Central Blindness Associated with a Pituitary Adenoma in a Mare - Daoualibi, Yasmin; Rocha, Juliana Ferreira; de Farias Brito, Marilene; da Silva Alonso, Luciano; Guimarães Ubiali, Daniel (Acta Scientiae Veterinariae, 2020)
Background: Pituitary pars intermedia (PI) adenoma is a benign adenohypophysis neoplasm, rare in Brazil, which may compress adjacent structures and lead to dysfunctions of the endocrine organs. The most affected species are equines, particularly aged animals. This neoplastic disease is often associated with Cushing’s syndrome, when the pituitary-adrenocortical axis is affected. However, this neoplasm is seldom associated with clinical blindness. This paper describes a case of pituitary pars intermedia (PI) adenoma which caused blindness in a mare. Case: An emaciated, blind mare that had difficulty finding water and food was referred to “Hospital Veterinário de Grandes Animais” of “Universidade Federal Rural do Rio de Janeiro”, in Seropédica, state of Rio de Janeiro, Brazil, and later to the “Setor de Anatomia Patológica” (SAP/UFRRJ) for necropsy. During necropsy it was found that the animal’s pituitary gland consisted of a circumscribed globous mass measuring 3.5x2.5x2.5 cm, symmetrical and well delimited at the sella turcica. Several organs were collected, fixed in 10% formalin and then processed for histological examination. The brain was subjected to serial cleavage along the path of the vision organs. All collected tissues were stained with hematoxylin and eosin; the pituitary was stained with Schiff Periodic Acid (PAS) to differentiate neoplastic cells and with Luxol Fast Blue to evidence demyelination. Histopathology found that the pars intermedia (PI) was thickened and compressed the neurohypophysis and adenohypophysis. Cells were arranged in a disorganized manner or formed follicles or cysts containing eosinophilic material (colloid), with granules strongly positive after staining with PAS. Proliferated cells were large, polyhedral to ovoid, and contained clear basophilic granular material. The nuclei were spherical to ovoid and there were light anisocytosis and anisocariasis. Cysts were frequently found in the pars intermedia (PI) and occasionally in the pars distalis. Mitoses were rare, less than one per field of greatest increase. In some areas of the pars intermedia (PI), cells were arranged in a solid manner forming spherical sub-nodules. An orange yellow pigment was observed in the pericary (lipofuscinosis) in various neurons of several areas of the central nervous system and of the trigeminal ganglion. In the optic tract, there were areas with moderate demyelination, evidenced by Luxol Fast Blue staining, and macrophages characterizing the so-called digestion chambers. In the right and left lateral geniculate nuclei a focal area of neurons with pyknotic and peripheral nuclei, marginal Nissl substance (central chromatolysis) and atypical and reactive astrocytes was observed, with increased volume, evident cytoplasm and nuclei with marginated chromatin which was sometimes reniform. Discussion: This paper presents the pathological findings obtained from a mare with central blindness due to pituitary pars intermedia adenoma. The analysis of the structures affected and correlation of alterations with the respective clinical signs are compared with alterations in other areas of the pituitary which generate clinical signals not observed in this mare, but which occur more often in equines with tumors in that organ. Thus, central and bilateral blindness was associated with compression of the optical tracts by the neoplastic mass and consequent death of neurons of the lateral geniculate nucleus. Pituitary PI adenoma should be considered as a differential diagnosis for blindness.